GREEN ECONOMY AND ENVIRONMENTAL SUSTAINABILITY: A LITERATURE REVIEW OF CHALLENGES AND OPPORTUNITIES - Loso Judijanto; Era Purike (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Green economy is a development concept that integrates economic and environmental aspects to achieve sustainable development. Although it offers important solutions, the implementation of green economy faces various challenges, both in terms of systemic, institutional, and community participation. This paper aims to review the literature related to the challenges and opportunities of implementing a green economy in the context of environmental sustainability. The results show that the main challenges in implementing a green economy include structural constraints in the economic system, institutional weaknesses, and lack of public participation and awareness. On the other hand, the green economy also offers various opportunities, such as the potential for new job creation, encouragement of technological innovation, broader economic benefits, and opportunities for international collaboration. Optimally utilising these opportunities can be an effective solution to address the challenges of sustainable development. The successful implementation of a green economy will be largely determined by the ability of stakeholders to overcome existing challenges and strategically capitalise on available opportunities. Strong integration of economic, social and environmental aspects is key to realising truly sustainable development.